Spatial distribution and transport characteristics of heavy metals around an antimony mine area in central China. (March 2017) - Li, Xin; Yang, Hong; Zhang, Chang; Zeng, Guangming; Liu, Yunguo; Xu, Weihua; Wu, Youe; Lan, Shiming
Abstract: The spatial distribution and transport characteristics of heavy metals in an antimony mine area (Xikuangshan, China) were systematically studied using a field survey and geostatistical analytical methods. In the study area, 52 soil and sediment samples were collected from bare land, grassland, woodland and river sediments covering a surface area of 20 km 2 . The soil properties and heavy metal concentrations were measured by wavelength dispersive X-ray fluorescence spectrometry and inductively coupled plasma-mass spectrometry, respectively. Correlation analysis and principal component analysis suggest that Cu, Zn, Cd, As, Pb and Sb can be attributed to anthropogenic inputs, whereas Cr, Mn and Ni are of natural origin. Distribution maps of heavy metals were generated using the Kriging interpolation method to identify their distribution trends. The results show the influence of wind, river, distance and vegetation on the spatial distribution. The results also revealed that windborne transport may play a significant role in the spreading of contaminants. In addition, the environmental risk of heavy metal pollution was evaluated using their geoaccumulation indexes in the whole region. All of the results indicate that the heavy metal distributions in the soils were consistent with the local prevailing wind direction. In addition, the environmental quality could be seriously threatened by heavy metal contaminants from the smelter and tailings. Graphical abstract: Highlights: ● As and Sb showed similar geochemical behavior on transport and deposition. ● Lower concentrations for Cr, Mn and Ni may be controlled by natural factors. ● Cu, Zn, Cd and Pb may be released from sulfide minerals. ● Heavy metal distribution trends were associated with local wind direction. ● The environment quality was obviously threatened by accumulation of Sb and Cd.